2010
DOI: 10.1249/mss.0b013e3181c3aa7e
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behaviors Increase Risk of Cardiovascular Disease Mortality in Men

Abstract: Purpose-To examine the relationship between two sedentary behaviors (riding in car and watching television) and cardiovascular disease (CVD) mortality in men in the Aerobics Center Longitudinal Study.Methods-Participants were 7,744 men (20-89 yr) initially free of CVD who returned a mailback survey during 1982. Time spent watching TV and riding in a car were reported. Mortality data were ascertained through the National Death Index till Dec 31, 2003. Cox regression analysis quantified the association between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
308
3
25

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(345 citation statements)
references
References 33 publications
9
308
3
25
Order By: Relevance
“…Previous studies reported the estimation of physical activity in females is difficult because domestic activity tends to be misclassified. 27 This may have occurred in our study for females. We may not have completely eliminated CVD survivors with severe after-effects, which could lead to a reverse causal relationship in our analysis.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies reported the estimation of physical activity in females is difficult because domestic activity tends to be misclassified. 27 This may have occurred in our study for females. We may not have completely eliminated CVD survivors with severe after-effects, which could lead to a reverse causal relationship in our analysis.…”
Section: Discussionmentioning
confidence: 71%
“…Asimismo, esta conducta ha sido relacionada con un aumento importante en el riesgo de muerte por enfermedad cardiovascular, diabetes tipo II, mortalidad por todas las causas, cáncer, etc. 34,[36][37][38] .…”
Section: Relación Entre Conducta Sedentaria Y Actividad Físicaunclassified
“…According to past studies, pro-inflammatory cytokines were found to be elevated in highly stressed individuals [15][16][17][18][19]. Physical inactivity and sedentary lifestyle were also found to be associated with increased risk of developing chronic low grade inflammatory states [20][21].…”
Section: Introductionmentioning
confidence: 97%